2017
DOI: 10.1016/s0140-6736(17)30059-4
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of patient age at intervention on risk of implant revision after total replacement of the hip or knee: a population-based cohort study

Abstract: SummaryBackgroundTotal joint replacements for end-stage osteoarthritis of the hip and knee are cost-effective and demonstrate significant clinical improvement. However, robust population based lifetime-risk data for implant revision are not available to aid patient decision making, which is a particular problem in young patient groups deciding on best-timing for surgery.MethodsWe did implant survival analysis on all patients within the Clinical Practice Research Datalink who had undergone total hip replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
421
4
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(473 citation statements)
references
References 23 publications
(36 reference statements)
12
421
4
7
Order By: Relevance
“…Both young (< 50 years) and old (> 90 years) age are thought to be relative contraindications to undergoing TKA. While younger people have a higher likelihood of requiring revision surgery (both earlier and during their lifetime), and although there is some evidence that clinical results may also be inferior in younger people, youth itself is not a contraindication. Young people can still experience benefits if they satisfy the criteria above.…”
Section: Patient Characteristics Influencing Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both young (< 50 years) and old (> 90 years) age are thought to be relative contraindications to undergoing TKA. While younger people have a higher likelihood of requiring revision surgery (both earlier and during their lifetime), and although there is some evidence that clinical results may also be inferior in younger people, youth itself is not a contraindication. Young people can still experience benefits if they satisfy the criteria above.…”
Section: Patient Characteristics Influencing Decision Makingmentioning
confidence: 99%
“…Young people can still experience benefits if they satisfy the criteria above. For the very old, important gains are also seen and the risk of revision is lower than for young patients . The concerns in older people reflect the risks of surgery in the presence of comorbidities rather than age per se.…”
Section: Patient Characteristics Influencing Decision Makingmentioning
confidence: 99%
“…Recently, a database study on 54.000 knee arthroplasties showed that joint replacement in patients under 55 years old increased the lifetime risk for revision up to 35%. is is questioning the impact of the increasing trend of more knee replacements in the younger patient's population [9]. Unfortunately, although alternative surgical procedures relying on scaffolds, tissue engineering, and cell transplantation have shown promising results in young patients with traumatic lesions, they provide less satisfying results and a low rate of return to sport in sport-active patients affected by cartilage degenerative lesions and OA [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium implants are an established treatment option for both dental and orthopaedic rehabilitation, particularly in an ageing population where demand is rapidly increasing (Srinivasan, Meyer, Mombelli, & Muller, 2017). Although 10-year survival rates of 94.6% for dental implants (Moraschini, Poubel, Ferreira, & Barboza Edos, 2015), 95.6% for total hip replacements and 96.1% for total knee replacements have been reported (Bayliss et al, 2017), failures do occur. Metabolic dysfunction such as type 2 diabetes mellitus (T2DM) has been shown to be associated with reduced dental implant survival rates (Naujokat, Kunzendorf, & Wiltfang, 2016) and an increased risk for revision of total hip replacements (Pedersen, Mehnert, Johnsen, & Sorensen, 2010).…”
Section: Introductionmentioning
confidence: 99%